Formulae for alpha square plus beta square

We know the formula i.e. a+b2 = a2+b2+2abSo from this we can write as α+β2 = α2+β2+2αβα+β2 = α2+β2+2αβα2+β2 = α+β2-2αβTherefore the formula is α2+β2 = α+β2-2αβ

  • 49

( a+b)square - 2ab or ( alpha +beeta ) - 2alphabeta

which gives, ( -b/a) - 2c/a

( since in a quadratic equation , alpha + beta = - b/a

and alphabeta= c/a )

now, taking asquare Lcm

b square- 2ac /a square

which is the require answer

and

  • 2

if this is help ful then plzz give thumbs up

plzzzzz...... :-)

  • 17
What are you looking for?